THE LIBRARY OF JERZY PLATER AS A MONUMENT OF BOOK CULTURE AND SCIENCE - KAUNAS, DOMAS (Knygotyra, 2011)
The object of this study was the personal library of Plater, a Lithuanian intellectual of the first half of the 19th century. The work on the article was inhibited by the lack of data from Jerzy Plater’s lifetime as the Plater family archive was destroyed by the Soviet Army which occupied Lithuania in 1940. The aim was achieved by analyzing dispersed published and unpublished historical sources and selecting the authentic data by comparing their reliability. The owner of the library was count Jerzy Plater (Jerzy Jan Wincenty Plater, Jerzy Jan Wincenty Plater-Broel z Broelu hrabia Plater, Georgius comes de Plater, Jurgis Plateris in Lithuanian; born 1810 in Klaipėda (Memel), died 1836 in Raseiniai, buried in Švėkšna) – a member of an influential aristocratic family in the Lithuanian–Polish Commonwealth. He was educated by domestic teachers in the manor, later in the Kražiai and Vilnius gymnasiums, and graduated from Vilnius University where he studied philology and liberal arts. At the University his scholarly interests were formed. Plater was one of the most important members of the gentry that participated in the Lituanistic movement of the first half of the 19th century. The main directions of scholarly work pursued by the Count were the Lithuanian language, history of Lithuania and his personal library. His works reflect the variety of methods applied by him: they included informal communication, targeted visits to the libraries that kept printed heritage collections, book analysis de visu, and archival research. The Count was one of the first authors to write his scholarly works in Lithuanian. Plater inherited the Gedminaičiai Manor from his parents and created a basis for his research there – a personal library and a small museum. To achieve his main aims, he built a Lituanistic collection which included not only publications, but also manuscripts, graphic art, technical drawings, paintings and museum objects. The collection comprised over 3000 items. The main acquisition sources were Vilnius and bookstores in the nearby Prussian towns Königsberg (Karaliaučius), Tilsit (Tilžė) and Klaipėda (Memel). There he acquired old Lituanistic and Old Prussian research works and serials. He sought for the possibilities to enrich his library through personal contacts with outstanding researchers, creative priests, and book culture representatives. The Count was aware of the advantages of collective research and invited a creative collaborator – the writer and philologist Simonas Tadas Stanevičius – to work with him. While working on this article, the author has identified 88 titles of the items that belonged to the library: 76 books, two volumes of a serial, one graphic design, and nine manuscripts. At present, they are scattered in Lithuania and abroad. The collected data provide a basis for describing the library structure in general by century, language and content. Five publications and manuscripts come from the 16th, seventeen from the 17th, 28 from the 18th, and 38 from the 19th century. As one could expect, most numerous is the collection of Polish books (19), but there were also 15 Latin books, 15 German, ten Lithuanian, and seven French books. The rest 12 books are printed in several languages: dictionaries of two or three languages and grammars of different languages, written in Latin or German with significant inclusions of linguistic examples from the target languages. These linguistic resources reflect the multilanguage environment of Plater, which included Lithuanian, Latvian, Greek, Latin, French, German, Polish and other big Slavic languages, such as Gud (Byelorussian), Russian, and Serbian. Thus, the linguistic composition of the library proves that its owner was well prepared for his investigations into historiography and linguistics. The fact of its existence proves also that the nation that lived under occupation was able to create its own possibilities for research, sense-making and future development. It is necessary to recreate this library as a virtual one. The further search for the library books or even their traces can be done only collectively. Plater deserves this effort because his library is worth of the status of a Lithuanian research and book culture monument.